PENGARUH KONSENTRASI GLUKOMANAN TERHADAP SIFAT FISIK SEDIAAN GEL ASAM ASKORBAT - Surya Sumantri Abdullah; Irma Antasionasti; Gerald Edward Rundengan; Ezrani Tasiam; Rezky Putri Indarwati Abdullah (Jurnal Farmasi Medica/Pharmacy Medical Journal (PMJ), 2024)
Gel preparations usually contain gelling agents which are critical factors that can affect the physical properties of the gel. The purpose to determine the appropriate variation of glucomannan concentration in the formulation of ascorbic acid gel on the physical characteristics of the gel. The research method began with the formulation of gel preparations using glucomannan as a gelling agent with variations in glucomannan concentrations at F1 (1%), F2 (1.5%) and F3 (2%). The gels were evaluated by their physical properties, including in the organoleptic, pH, homogeneity, adhesion, and spreadability tests. The research showed that in the pH and adhesiveness tests, increasing the concentration of glucomannan could increased the pH and adhesiveness of the gel. However, the spreadability of the gel decreased with increasing glucomannan concentration. The gel formula with 2% glucomannan concentration (F3) showed higher adhesion, as well as higher pH, although the gel spreadability decreased. From the evaluation results, all meet requirement for physically stable.